Development of Power Assembly Technology for Wind Power Converters - CHEN Yanping; JIANG Yunfu; XIN Lanyuan (Kongzhi Yu Xinxi Jishu)
Power assembly is the key component of wind power converter, whose performance and reliability affect the performance and reliability of converter. For IGBT power assembly in wind power converter, it introduced its key technoligies such as circuit topology & composition structure, key device selection, gate-driver technology, heat dissipation technology and its development trend, which could provide references for the design, selection and technical research of power assembly in wind power converter.